From the world of the consumption to the consumption -world. Lipovestky and the paradoxes of the individualism and democratic consumerism - Durán Vázquez, José Francisco (Nómadas. Critical Journal of Social and Juridical Science, 2011)
In this article there are described the fundamental ideas of Lipovestky's thought, showing as the consumption it has turned into his work into a total, valid phenomenon to interpret almost any aspect of the social reality. It ends up by being said that, though his interpretations are full of rich and suggestive ideas on the contemporary society, also have been simplified in excess on having linked almost all the social facts, for more contradictory than these be, to the common reason of the consumption, not analyzing with the due rigour and severity many of the phenomena that it describes.
Keywords: Lipovestky; consumption; individualism; paradoxes